A cross-sectional survey on wounds in horses in New Zealand. Issue 2 (3rd March 2016) - Theoret, CL; Bolwell, CF; Riley, CB
Abstract: AIM: To determine the frequency and type of skin wounds encountered by New Zealand veterinarians in their equine patients, the duration and estimated costs of treatment as well as the expected outcomes for these wounds. METHODS: An online survey was sent to all veterinarians registered with the New Zealand Equine Veterinary Association. The survey comprised questions on the location and experience of respondents, the number of wound-related cases in relation to the total equine caseload, the type and anatomical location of wounds treated, the frequency, duration and costs of treatments, the outcome of wound treatment and an estimate of the most common causes of death or euthanasia in their equine patients. RESULTS: The survey response rate was 110/262 (41.9%). The median number of equine cases seen by respondents was 20 (interquartile range (IQR) 6–60) per month; of these, five (IQR 2–10) were wound related. Wounds ranked third after lameness and respiratory disease for the relative frequency with which respondents encountered them. Of 102 respondents 59 (58%) reported that their clients frequently treated wounds incurred by their horse without consulting a veterinarian. Wounds on the distal limb, whether involving only the skin or also deeper structures, were reported by 86/101 (85%) respondents as the most frequently encountered. Wounds in this location also incurred the longest treatment period and were the most prone to develop complications. Finally, wounds ranked second, after colic, as the most common cause of death/euthanasia in the veterinary respondents' equine patients. CONCLUSIONS: The data obtained via the survey indicate that skin wounds, particularly on the distal limb, are a common occurrence in horses in New Zealand and, when they involve structures underlying the skin, are costly and time-consuming to manage and may lead to decreased performance, retirement or euthanasia. Consequently, we recommend that more effort be devoted to the education of equine veterinarians and owners, and that appropriate research funds be allocated to help improve patient outcomes.